Reading the urban socio-spatial network through space syntax and geo-tagged Twitter data - Iranmanesh, Aminreza; Atun, Resmiye Alpar (Routledge Journals, Taylor & Francis Ltd, 2020)
This research examines the predictability of geo-tagged Twitter data via space syntax integration measurement using geographic information system (GIS). Mobile networking mediums are an emergent part of everyday life in the city. In light of this, research on cities needs to take into account these new data sources. The study was conducted in two Cypriot cities, Famagusta and Kyrenia, and the result shows the significance of local accessibility in predicting Twitter data in both cases. The outcome also suggests the critical importance of investigating the outliers in the dataset because they might clarify hidden potentials of urban spaces.
Keywords: Social Media; Land-Use; Big Data; City; Movement; Configuration; Environment; Famagusta; Locate; Parks